A Christmas engagement : an Amish romance - Byler, Linda (Good Books, 2021)
"Liz looked up to find his eyes on hers, with an expression completely undecipherable. Instantly, the words she had been planning to say became [e]mbedded in her throat, her knees weakened, and all common sense evaporated." -- Back cover.